Clinically Historical and Prospective Associations Between Learning Disorders and Concussion in Young Adult Athletes. Issue 2 (March 2020) - Pagani, Linda S.; Ellemberg, Dave; Moore, Robert Davis
Background . Athletes with specific learning disorder (LD) tend to score lower on neuropsychological tests and are at increased risk of personal injury than their counterparts without such disorders. Using a retrospective historical and prospective design, we examined whether adult athletes with LD, the most prevalent of neurodevelopmental disorders, experience greater chances of past and future concussions than their counterparts without LD. We expected to find that young athletes with LD would show greater risk of past (historical) and future (prospective) cerebral concussions. Methods . Participants (95 men and 53 women aged 18 to 25 years) were recruited from university sports teams and followed during an entire season. Of these, 38 participants had a history of LD and 101 had a history of at least 1 concussion (72 males, 29 females) at the preseason baseline. One-third experienced a new concussion. Data analytic procedures include inferential cross-tabulations. Results . Athletes with LD were twice more likely to have a concussion history at baseline and to have a history of multiple concussions than athletes without LD; 95% CI = [0.86, 4.92] and [0.77, 3.40], respectively. Athletes with LD were twice more likely to incur a new concussion than those without LD; 95% CI = [0.86, 4.92]. Conclusions . Adult athletes with LD experience greater chances of previous and future concussions compared with counterparts without LD. Preventive practices regarding individuals with neurodevelopmental disorders may not only prevent the biopsychosocial consequences of brain trauma for the individual, but also represent a cost-effective public health measure.